PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 036 SINTONG - Aryani Aryani; Eddy Noviana; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this research is that the students' learning outcomes are still categorized low because students still have difficulty in accepting lessons, the less teachers involve the students in learning and the teacher only uses the lecture method and the students are less directly involved to determine their own knowledge. From these problems need to be done Classroom Action Research (PTK) with the title Application of Problem-Based Learning Model. This study aims to improve the learning outcomes of Science Class III SDN 036 Sintong Tanah Putih District with the number of students sebanayak 20 people. This study was conducted with two cycles, each cycle consisting of two meetings with one daily test. Instrument of data collection in this research is student activity sheet and teacher activity sheet and student's daily test result. Analysis of teacher activity data in cycle I of meeting I is 60.00% and the second meeting is increased to 70.00%. at Ilu II meeting II is 85.00% and the second meeting increases again to 90.00%. Furthermore analysis of student activity result on first cycle of first meeting 60.00% and second meeting increased to 75.00%. in the second cycle of the first meeting 80.00% and at the second meeting increased again to 85.00%. then the results of this analysis can be concluded the student learning outcomes increased, it also proved the average student learning outcomes on the basic score is 65.00 and in the first cycle to 68.50 and in the second cycle increased again to 76.75. Completed learning outcomes on the basic score of 8 people (40%), cycle I to 13 people (65.00%) and increase again in cycle II to 18 people (90.00%)Keywords: Problem Based Learning Model, Learning Outcomes of Science